The Dyad School Success/Failure in the Academic Development of the Working Class Women from Mendoza - Mercedes Molina-Galarza (Revista Electrónica Educare)
The notion of academic performance renders account of the results achieved by the students during their school education.  Internally, there are two opposed phenomena:  school success and school failure.  Sociology of education has contributed to the discussion of both notions revealing their social nature closely related to the institutional and socio-cultural contexts in which education is developed.  This paper is the result of a research project conducted for our doctoral thesis.  Its purpose is to contribute to enlighten the scopes of this discussion, by analyzing the school development of a group of working class women from Mendoza. We were interested, in the first place, in knowing the reasons why they quit school when they were young girls or adolescents.  Subsequently, we have approached the opportunities they had to access the system again during their adulthood, the obstacles they had to face and the resources to be able to complete the medium level.